Tinjauan Literatur: Pengaruh Parameter Metode Kromatografi Lapis Tipis untuk Identifikasi Kafein dalam Kopi - Hariadi, Nayla Nur Azkia; Basmalah, Nur; Laprilski , Dewi Hanun; Azzahra , Khaerunisa; Mulki , Munir Alinu (Journal of Pharmaceutical and Sciences, 2025)
Background: The rising consumption of coffee in Indonesia necessitates reliable methods for caffeine analysis to ensure product quality and safety. Thin Layer Chromatography (TLC) is a simple, effective, and polarity-based technique widely used for the qualitative identification of compounds like caffeine in coffee. However, the results of TLC analysis are highly dependent on several methodological parameters. Objectives: This literature review aims to identify and analyze the critical parameters of the TLC method—including the mobile phase, stationary phase, visualization techniques, and sample preparation—that influence the effectiveness of caffeine identification in coffee. Methods: A systematic literature review was conducted using online databases (Google Scholar, PubMed, Semantic Scholar, and Crossref). Articles from the last ten years were selected based on inclusion and exclusion criteria, resulting in nine primary studies for in-depth analysis. Results: The review confirms that silica gel 60 F254 is the most effective stationary phase. The composition of the mobile phase is crucial; a mixture of dichloromethane:methanol (9.5:0.5) was found to be optimal for separating caffeine, yielding Rf values within the ideal range of 0.3–0.7. Visualization under UV light at 254 nm successfully detected caffeine as dark spots. Sample preparation techniques, particularly reflux and ultrasonic extraction, significantly enhanced extraction efficiency and detection sensitivity. Factors such as mobile phase stability, spotting technique, and sample matrix were also identified as key influencers on the chromatographic results. Conclusion: TLC is an efficient and cost-effective method for the qualitative identification of caffeine in coffee. Its success is determined by the optimization of critical parameters, primarily the mobile phase composition. While excellent for initial screening, TLC requires complementary techniques for precise quantitative analysis. Future work should focus on standardizing these parameters to improve the reproducibility and reliability of caffeine analysis using TLC.